2013
DOI: 10.1371/journal.pone.0054664
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Gene Expression Analysis Reveals Casiopeína-Induced Apoptosis Pathways

Abstract: Copper-based chemotherapeutic compounds Casiopeínas, have been presented as able to promote selective programmed cell death in cancer cells, thus being proper candidates for targeted cancer therapy. DNA fragmentation and apoptosis–in a process mediated by reactive oxygen species–for a number of tumor cells, have been argued to be the main mechanisms. However, a detailed functional mechanism (a model) is still to be defined and interrogated for a wide variety of cellular conditions before establishing settings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…These copper complexes have been developed primarily for their action against cancerous tumors [14,15,16] in in vitro and in vivo models. Although the action mechanism is not known in detail, at the molecular level, several results support that these compounds are able to inhibit cell proliferation mainly by apoptotic pathways [15,16], that participate in redox reactions that produce reactive oxygen species [15,16] and interact directly with DNA and its constituents [17].…”
Section: Introductionmentioning
confidence: 99%
“…These copper complexes have been developed primarily for their action against cancerous tumors [14,15,16] in in vitro and in vivo models. Although the action mechanism is not known in detail, at the molecular level, several results support that these compounds are able to inhibit cell proliferation mainly by apoptotic pathways [15,16], that participate in redox reactions that produce reactive oxygen species [15,16] and interact directly with DNA and its constituents [17].…”
Section: Introductionmentioning
confidence: 99%
“…IPA has been extensively used in biomedical research (having almost 9,000 citations (7)) to analyze big data because its Ingenuity Knowledge Base is the largest curated database of biological and chemical interactions, extracted from the scientific literature (7,14). By using IPA's bioinformatics tools to search the knowledge base, we have identified several potential novel molecular targets for the treatment of SNHL and prioritized human testing of drugs that have shown promise in animal studies.…”
mentioning
confidence: 99%
“…The need to carry out physicochemical studies in order to determine the aggregation properties of this compounds is of great importance since other compounds of the family of the Casiopeínas have also shown antitumor and anti-protozoan activity [7, 2426]. …”
Section: Resultsmentioning
confidence: 99%
“…Experimental observations showed that different members of the family of the Casiopeínas present nuclease activity in contact with DNA, comparable to that shown by other metal complexes [6]. These results allowed to design and perform an experiment of the whole genetic expression of tumor cells exposed to Casiopeínas, where it was found that particular pathways related with the cell cycle, gene expression, cellular growth, proliferation and cell death were affected, all of them related with oxidative stress and DNA damage [7].
Fig.
…”
Section: Introductionmentioning
confidence: 84%